Promosi kesehatan remaja melalui program pediatric social responsibility (PSR) di Nusa Tenggara Barat - Karuniawaty, Titi Pambudi; Dewi, Nurhandini Eka; Wiguna, Putu Aditya; Sulaksmana, Wayan Sandhi; Sari, Linda Silvana; Atuzzaqiyah, Rifa; Nailul, Nur; Mufidah, Laily; Hapsari, Indri; Saril, Lenny Puspita (INDRA: Jurnal Pengabdian kepada Masyarakat, 2024)
Adolescents needs serious attention because they are at risk of experiencing various health problems. The Pediatric Social Responsibility (PSR) initiated by the Indonesian Pediatric Society, is an innovation program to overcome the health problems of Indonesia adolescents through assistance to health workers who work at primary health centers in various subject including adolescent health promotion. One of its activities in West Nusa Tenggara was carried out in a hybrid seminar aimed to increase knowledge of health workers and related stakeholders regarding adolescent health with a school-based approach. A total of 289 participated in this activity, with 149 (51.6%) participants attending offline Program evaluation was carried out by comparing the knowledge of participants before and after the activity (pre-test and post-test) and evaluating the implementation of the activity. There was a significant difference of participants' knowledge before and after the activity (p-value=0.005; p<0.05). This program was useful (82.2%), held in a sufficient time duration (90.1%), the material was updated (72.9%) and in accordance with the needs of the participants (89.1%), also might be applied in daily work/practice. Similar activities in this PSR program need to be held again regularly with a wider coverage, varied themes and involve teenagers directly.